THE ROLE OF RADIOTHERAPY IN THE TREATMENT OF EWING SARCOMA OF THE BONE - Filipovic, Predrag; Popović Vuković, Marija; Nikitovic, Marina (Medical Research, 2023)
Ewing sarcoma (ES) is the second most common primary bone malignancy after osteosarcoma. The disease most often occurs in adolescence, with peak incidence around the age of fourteen. The most common primary location of the tumor is the bones of the pelvis, followed by the ribs, spine and long bones of the extremities such as the tibia and fibula. ES shows a tendency towards hematogenous dissemination, primarily in the lungs and bones, much less often lymphogenously. One third of patients have distant metastases present at initial diagnosis, which is why ES is considered a systemic disease. The treatment of Ewing sarcoma is based on a multimodal approach that includes the use of chemotherapy, surgery and/or radiotherapy. The identification of prognostic parameters enabled the individual treatment of patients based on the assessed risk group. With the application of modern therapeutic protocols, five-year survival for patients with localized disease lies between 60% - 68%, while for patients with metastatic disease, five-year survival is still unsatisfactory and is around 17%. ES belongs to the group of radiosensitive tumors, and radiotherapy plays a very important role in local control of the disease, in combination with surgical treatment or independently and can be applied as radical, preoperative or postoperative radiation therapy. Also, radiation therapy has a role in the palliative approach in the treatment of lung metastases and other metastatic sites. Considering that the modern multimodal treatment of Ewing sarcoma leads to long-term survival, it is necessary to take into account the expected side effects of therapy that can reduce the quality of life of treated patients. Modern radiotherapy techniques such as three-dimensional conformal radiation therapy (3D CRT), intensity modulated radiation therapy (IMRT), volumetric modulated arc therapy (VMAT) enable precise delivery of the prescribed dose of radiation to target volumes with better sparing of surrounding normal tissues and organs, which leads to to a lower incidence of late sequelae of radiation therapy and enables preservation of the quality of life of treated patients.